Synthesis and Antimicrobial Evaluation of Some Thiazole Derivatives - Bhuiyan, M. H.; Rahman, A. F. M. H. (Journal of Scientific Research, 2010)
Reaction of 2-amino-4-phenylthiazole with various aromatic aldehydes afforded 2-arylideneamino-4-phenylthiazoles. On the other hand treatment of 2-amino-4-phenylthiazole with several acyl halides furnished N-(thiazol-2-yl)-amides. The synthesized compounds have been screened for their antimicrobial activity against Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Shigella dysenteriae, Salmonella typhi, Pseudomonous sp. bacteria and Aspergillus niger, Penicillium notatum, Aspergillus funiculosus, Collectrichum corchori Ikata (Yoshida) and Curvularia lunata fungi respectively. Some of the synthesized compounds exhibited pronounced antimicrobial activities. Keywords: Aminothiazole; Arylideneaminothizole; N-(Thiazol-2-yl)-amide; Antimicrobial activity. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.5419 J. Sci. Res. 3 (1), 111-119 (2011)